Selective Chemical Labeling and Sequencing of 5-Hydroxymethylcytosine in DNA at Single-Base Resolution - Li, Xiaogang; Shi, Xinxin; Gong, Yin; Guo, Wenting; Liu, Yuanrui; Peng, Chunwei; Xu, Yingchun (Frontiers in Genetics, 2021)
5-Hydroxymethylcytosine (5hmC), the oxidative product of 5-methylcytosine (5mC) catalyzed by ten-eleven translocation (TET) enzymes, plays an important role in many biological processes as an epigenetic mediator. Prior studies have shown that 5hmC can be selectively labeled with chemically-modified glucose moieties and enriched using click chemistry with biotin affinity approaches. Besides, DNA deaminases of the AID/APOBEC family can discriminate modified 5hmC bases from cytosine (C)or 5-methylcytosine (5mC). Herein, we developed a method based on ESC whole-genome analysis which could enrich 5hmC-containing DNA by selective chemical labeling and locate 5hmC sites at single-base resolution with enzyme APOBEC-based deamination. The combination experimental design is an extension of previous methods, and we hope that this cost-effective single base resolution 5hmC sequencing method could be used to promote the mechanism and diagnosis research of 5hmC.